Experiences and barriers to accessing mental health support in mothers of children with a disability. (24th May 2021) - Gilson, Kim‐Michelle; Davis, Elise; Gains, Joan; Brunton, Susan; Williams, Katrina; Reddihough, Dinah
Abstract: Background: Despite evidence for high levels of mental health problems in mothers of children with a disability and the potential impact on caring for their child, very little is known about mothers' experience in accessing professional mental health support. This study aimed to explore mothers' views and experience on seeking help for their mental health. Methods: Semi‐structured interviews were conducted with 25 mothers of children with a disability. Thematic analysis was completed. Results: Mothers experienced significant barriers when accesing support at the personal, professional and system level. Personal barriers included the need for competency and stigma about mental illness: professional barriers included the lack of discussions about mental health and interpersonal factors that hindered disclosure. System barriers included feeling invisible to the health services, paediatric care focusing on the child rather than the family and limitations to the type of mental health support available. Conclusion: Mothers perceive substantial barriers in accessing support for their mental health. It is important that strategies are designed so the importance of mentally healthy mothers is understood and to normalize a need for assistance when you are the mother of a child with additional support needs. Strategies are also needed to encourage mothers to seek help and to assist professionals having discussions about maternal wellbeing. Improvements are also required in the accessibility of service supports.